2020
DOI: 10.1108/hff-07-2019-0597
|View full text |Cite
|
Sign up to set email alerts
|

A cubic B-spline quasi-interpolation method for solving two-dimensional unsteady advection diffusion equations

Abstract: Purpose The purpose of this study is to extend the cubic B-spline quasi-interpolation (CBSQI) method via Kronecker product for solving 2D unsteady advection-diffusion equation. The CBSQI method has been used for solving 1D problems in literature so far. This study seeks to use the idea of a Kronecker product to extend the method for 2D problems. Design/methodology/approach In this work, a CBSQI is used to approximate the spatial partial derivatives of the dependent variable. The idea of the Kronecker product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The fifth step is to use the trust level prediction model to make predictions, and finally end the process. Data preprocessing mainly involves interpolating missing data, and there are three traditional interpolation methods, namely elimination, single interpolation, and multiple interpolation [14]. Due to the uneven distribution of missing data, the processing of missing data is achieved through single and multiple interpolation methods.…”
Section: Calculation and Prediction Methods Construction Of Interacti...mentioning
confidence: 99%
“…The fifth step is to use the trust level prediction model to make predictions, and finally end the process. Data preprocessing mainly involves interpolating missing data, and there are three traditional interpolation methods, namely elimination, single interpolation, and multiple interpolation [14]. Due to the uneven distribution of missing data, the processing of missing data is achieved through single and multiple interpolation methods.…”
Section: Calculation and Prediction Methods Construction Of Interacti...mentioning
confidence: 99%
“…Greville (Khalid et al, 2020) additionally stated that spline curves can be used in numerical methods during the same period. Mittal et al, (2020) also demonstrated the concept of the presence and uniqueness of specific bicubic splines. Majeed et al, (2020); Ahlberg, et al, (1965) studied the minimal normal characteristics of basic spline curves.…”
Section: Introductionmentioning
confidence: 94%
“…Case 2: Consider the two-dimensional inhomogeneous unsteady convection-diffusion equation as given in [47] ( )…”
Section: Numerical Testmentioning
confidence: 99%